Pengaruh Lean, Agility dan Collaboration Terhadap Sustainability Outcome Dalam Humanitarian Supply Chain Management (HSCM) Performance Pada Fase Tanggap Darurat Bencana - Lukas, Yoram Alfi; Santosa, Wahyuningsih; Dewayana, Triwulandari Satitidjati (Jurnal Locus Penelitian dan Pengabdian, 2025)
Humanitarian organization currently facing the challenges to ensure the indicator of sustainability outcomes (SO) are achieved during the their first phase response in calamity. Humanitarian supply chain management in its perfomance (HSCM) reflected their efficiency and effectiveness of the operations. In the strategic view lean practice (LP), agility practice (AP), and collaboration (CO) are highly contributed to ensure the HSCM perfomance and SO are achievable. This study aims to investiges the influence of LP, AP and CO mediates by HSCM performance to achieve the SO’s indicators in the disaster emergency response phase. Research methodoloy used is quantitative and descriptive analysis with purposive sampling to the government institution, humanitarian organizations, national red cross organization and other civil society organizations work in the disaster and humanitarian response. Various respondent’s positions in supply chain, technical in program and other support functions. Data collected via online questionnaire and were distributed to 209 respondents. The findings of this research show that the CO mark strong positive effect to HSCP and SO, LP made positive effect to HSCP but negative effect to SO, AP mark negative effect to HSCP and last HSCM-P to SO moderate positive effect. This research marked a LP is significantly improved HSCM-P contributed to the achievement of sustainable indicators. It is the evidence that collaboration (CO) can be the main focus of humanitarian organization to achieve the sustainability outcome (SO) indicators. Future studies study suggest to expand the dimension in Lean Practice to contribute to Sustainability outcomes.